PVA stabilized gold nanoparticles by use of unexplored albeit conventional reducing agent - Khanna, P. K.; Gokhale, R.; Subbarao, V. V. V. S.; Vishwanath, A. K.; Das, B. K.; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2005)
Poly(vinyl alcohol) (PVA) stabilized gold nanoparticles have been prepared in aqueous medium using two different reducing viz.; hydrazine hydrate, a stronger reducing agent and sodium formaldehydesulfoxylate (SFS), a slightly weaker reducing agent. SFS is used for first ever time for reduction of gold metal salt. The PVA stabilized gold nanoparticles solutions are wine red to blood red coloured and are stable over a long period of time with no indication of aggregation. The solution shows strong visible light absorptions in the range of 520-540 nm, characteristics of gold nanoparticles. Powder X-ray diffraction patterns of freshly prepared films containing gold nanoparticles indicated particles size to be about 15 nm. Transmission electron microscopy (TEM) of a more than two-week-old sample revealed well-defined non-agglomerated spherical particles of about 50 nm diameter in solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Nanostructures; Polymer